2018
DOI: 10.7554/elife.31662
|View full text |Cite
|
Sign up to set email alerts
|

Functional role of the type 1 pilus rod structure in mediating host-pathogen interactions

Abstract: Uropathogenic E. coli (UPEC), which cause urinary tract infections (UTI), utilize type 1 pili, a chaperone usher pathway (CUP) pilus, to cause UTI and colonize the gut. The pilus rod, comprised of repeating FimA subunits, provides a structural scaffold for displaying the tip adhesin, FimH. We solved the 4.2 Å resolution structure of the type 1 pilus rod using cryo-electron microscopy. Residues forming the interactive surfaces that determine the mechanical properties of the rod were maintained by selection base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
63
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 79 publications
(65 citation statements)
references
References 81 publications
2
63
0
Order By: Relevance
“…Similar local strand unwinding has been observed for chaperone-usher pili. Near-atomic resolution structural analysis of the corresponding pili with cryo-EM revealed that the unwinding of the helical assembly occurred analogously at the weaker axial interface (44)(45)(46).…”
Section: Discussionmentioning
confidence: 99%
“…Similar local strand unwinding has been observed for chaperone-usher pili. Near-atomic resolution structural analysis of the corresponding pili with cryo-EM revealed that the unwinding of the helical assembly occurred analogously at the weaker axial interface (44)(45)(46).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, such experiments showed that type 1 pilus rods require slightly higher forces to induce rod unwinding than do P pilus rods, prompting the suggestion that type 1 pili are better adapted to withstand the more turbulent flows of the lower urinary tract (36,76). Several structures of the type 1 pilus rod have been determined (10,77,78) (Fig. 3), revealing a very similar overall architecture to the P pilus rod, except that the type 1 pilus rod lacks the so-called "staple" region (9) (Fig.…”
Section: Clinging On: the Importance Of The Pilus Rodmentioning
confidence: 99%
“…Crude sheared fractions of strains BW25113 F′ expressing ppdD (from pCHAP8565) and either the T2SS genes (from pCHAP8184) (panels A‐C) or T4PS genes (from pMS41) (panels D‐F) were analysed. Black arrows indicate Type 1 pili (in panels B and C) as shown previously in (Spaulding et al, ), the blue arrow indicates flagella (in panel E) and white arrows indicate PpdD T4P. The scale bar (A) is 50 nm.…”
Section: Resultsmentioning
confidence: 99%